A new species of Chaetozone (Polychaeta, Cirratulidae) from the Bay of Biscay offshore France, together with a review of Chaetozone species from the North Atlantic and adjacent waters - Blake, James A.; Lavesque, Nicolas (Zootaxa, 2017)
A new cirratulid species of the genus Chaetozone has been discovered offshore in fine muddy sediments in the Bay of Biscay, France. This species is unusual in having an expanded fusiform anterior body region and numerous subdermal glands along the entire body that produce an elaborate and distinctive pattern when stained with Methyl Green. The new species is compared with closely related congeners and a review of Chaetozone species from the North Atlantic Ocean is presented.